The Use Of Innovative Technologies In Organizing The Professional Training Of Teachers In The Field Of Technological Education - Muborak Sobirovna Abdullayeva (Euro Asian Journal Publishing, 2024)
The article provides for the improvement of students' professional training, analyzes the stages of modern lessons, and methods of using innovative technologies in the lesson process
Keywords: cluster approach; professional training; electronic platform